STRATEGI PENGEMBANGAN AGROINDUSTRI MINYAK KAYU PUTIH DI KAMPUNG RIMBA JAYA DISTRIK BIAK TIMUR KABUPATEN BIAK NUMFOR - Runtuboy, Joebell Sonia; Agatha W. Widati; Darmawanto Uria; Saut M. P. Simanungkalit (Sosio Agri Papua, 2025)
This study aims to identify the development potential of the cajuput oil agroindustry in Biak Numfor, assess internal and external factors influencing its development, and formulate appropriate strategies. Using descriptive methods and SWOT analysis, this study reveals that the cajuput oil agroindustry in Rimba Jaya Village has significant potential, supported by high-quality products meeting national standards with 70% cineole content. However, market access and selling prices remain challenging. Government support through promotion and technical assistance offers significant opportunities for expansion. Based on the analysis, strategies focusing on market access expansion and production capacity enhancement are recommended.